Management of glaucoma in a case of familial aniridia by trabeculectomy - Barthakur, R; Shrestha, SP; K, S Bhat; Natarajan, M (Nepalese Journal of Ophthalmology, 2010)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Aniridia is a rare developmental disorder. Glaucoma and complications associated with glaucoma surgery are a major cause of blindness in patients with aniridia. We describe here a case of a nine year old boy who presented with familial aniridia of both eyes along with glaucoma. He was treated by trabeculectomy of both eyes, which was successful in controlling the glaucoma. Key words: Aniridia; glaucoma; trabeculectomy DOI: 10.3126/nepjoph.v1i1.3677 Nep J Oph 2009;1(1):75-76